2011
DOI: 10.1002/hed.21884
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of capecitabine plus cisplatin as first‐line therapy in patients with metastatic nasopharyngeal cancer

Abstract: Capecitabine plus cisplatin is an active first-line combination in metastatic NPC that requires a short hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…However, the incidence rate is not higher than 1 per 100,000 people in Western countries (Zhou et al, 2007, Yu and Yuan, 2002). Unfortunately, distant metastasis is a main cause of death for NPC patients, which often has an unfavorable prognosis (Chen et al, 2012, Chua et al, 2012, Liu et al, 2003). Although computed tomography (CT) and magnetic resonance imaging (MRI) are effective, they cannot accurately provide a prognosis for NPC or predict the effectiveness of biological therapeutic targets (Lin et al, 2013, Gong et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence rate is not higher than 1 per 100,000 people in Western countries (Zhou et al, 2007, Yu and Yuan, 2002). Unfortunately, distant metastasis is a main cause of death for NPC patients, which often has an unfavorable prognosis (Chen et al, 2012, Chua et al, 2012, Liu et al, 2003). Although computed tomography (CT) and magnetic resonance imaging (MRI) are effective, they cannot accurately provide a prognosis for NPC or predict the effectiveness of biological therapeutic targets (Lin et al, 2013, Gong et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…[510] Unfortunately, patients with distant metastasis have been demonstrated with even worse survival outcome, the progression-free interval (PFS) was only 7.3 to 10 months. [1113] Because the application of additional treatment could cure or prolong the survival time in 10% to 20% of patients with local or distant progression, [14] thus there is pressing need to identify the high-risk patients with poor prognosis so that novel and intensive protocols could be initiated earlier to improve survival.…”
Section: Introductionmentioning
confidence: 99%
“…A phase II study in Chinese patients showed that the combination of capecitabine and cisplatin was effective and well-tolerated as a first-line treatment among metastatic NPC patients [27]. Similarly, Chua et al [19] conducted a multicenter phase II study involving 39 patients with metastatic NPC and reported that the overall response rate was 53.8% and the median OS was 28.0 months. However, due to the limitation of the small sample size, it was difficult to get the exact conclusion on whether capecitabine could further prolong the survival of patients with metastatic NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chua et al. [19] conducted a multicenter phase II study involving 39 patients with metastatic NPC and reported that the overall response rate was 53.8% and the median OS was 28.0 months. However, due to the limitation of the small sample size, it was difficult to get the exact conclusion on whether capecitabine could further prolong the survival of patients with metastatic NPC.…”
Section: Discussionmentioning
confidence: 99%